ANALISIS PENGARUH TINGKAT CORPORATE RISK DISCLOSURE (CRD) TERHADAP BIAYA MODAL EKUITAS DAN KINERJA PERUSAHAAN (Studi empiris terhadap perusahaan bank yang terdaftar di BEI yang telah diaudit pada tahun 2015-2017) - Haritz Faiz Heryantama; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2019)
This study aims to examine the effects of level of corporate risk disclosure) to the cost of equity capital and company performance. Controlling variables in this study include the ratio of equity market value to equity book value, leverage ratio, firm size, independent audit committee, consumer price index and auditor type. The sample population of this study uses a registered and audited banking company on the Indonesia Stock Exchange in period of 2015 - 2017. The research sample was obtained using a purposive sampling method, with a total sample of companies collected as many as 102. This study uses multiple linear regression based on ordinary least square for hypothesis testing. The final results of this study conclude that the independent variable risk disclosure of the company has a negative influence on the cost of equity capital and the level of corporate risk disclosure has a positive effect on company performance.